Appointment of Four Judges in Fāṭimid Egypt in 525/1131, A New Interpretation - İrfan İnce (İslam Tetkikleri Dergisi)
The appointment of four judges in the Fatimid state in 525/1131 was significant enough to prompt an anonymous source to document it, and it was later taken up by modern scholars, who speculated about its meaning in its historical context. This event offers valuable insights into the Fāṭimid socio-political history and the history of Islamic law. Notably, two of these judges were from two Shīʿa schools and the other two from two Sunnī schools. A local source, writing approximately half a century after the event, described it as an unprecedented occurrence in the Muslim community. While the exact implications of this statement remain ambiguous, modern scholars have found it both intriguing and instructive in their interpretations. The appointment record does not specify any restrictions on the jurisdiction of judges concerning cases they can adjudicate. However, their authority over inheritance matters was emphasized. Certain fundamental rulings where Shīʿa and Sunnī doctrines diverged were associated with the Fāṭimid conception of imāmate. For the same reason, the Fāṭimid Rulers adopted a stringent stance on these matters during the early stages of their rule in Egypt. Therefore, this information provides significant insights into the Fāṭimid judicial system, the application of Shīʿa law in a predominantly Sunnī Egyptian society, and the socio-political context of its enactment. Conversely, the limited availability of historical sources from this period enhances the value of this information and, while at the same time, complicates its interpretation. Allouche was the first researcher to explore this historical information extensively, attempting to determine the political motivations behind the appointments and the status and identities of the appointed judges within the constraints of limited sources. Subsequent literature frequently referenced Allouche’s work, but no alternative interpretations were proposed. In this paper, I first address a question overlooked by Allouche by identifying the primary source of this historical information. I try to demonstrate how this isolated piece of knowledge was integrated into the main text, which significantly contributed to difficuties in its interpretation. Subsequently, I examine Allouche’s method of using the sources, highlight significant gaps and errors in his source analysis, and suggest revisions for his evaluation of the main questions he tried to answer.